Deformation behavior of crosslinked polyurea elastomers obtained via sol-gel chemistry: Experimental determination and constitutive modelling - Rull, Nahuel (2020)
The mechanical behavior of three crosslinked polyurea (PU) elastomers obtained by sol-gel chemistry under uniaxial monotonic and cyclic tests has been assessed. These elastic networks are composed of hard and soft domains, where the segmental molecular weight between crosslinking points differs among the samples and allow studying the effect of this parameter on the mechanical properties. In this paper, uniaxial tension tests were performed in order to capture the main characteristics of the stress-strain behavior of these PU elastomers, e.g., non-linear hyperelastic behavior, hysteresis, and softening. In addition, a constitutive model that properly represents their behavior was proposed showing that the non-linear stress-strain behavior at large strain values exhibits strong hysteresis and softening.